Can anyone tell me how to change a function from f(x)= to y=f(x)
for example. If the equation was f(x)=-5+3x how would I change it to y=f(x)
I got a question like this on a quiz and I did not understand it. It also asked to graph it.
I have more information upon request.
F(x) is just a substitute for y it means that y is a function of x
f(x) = 3x+2 is the same as y = 3x+2
So its just a different way of saying it?
When I graphed it on google it says the Y-intercept is oh. I'm so dumb. I chose the graph that looked most similar to it instead of looking at the x and y-intercepts. Im so dumb